OXIDATIVE STRESS IN PATIENTS WITH VULVAR KRAUROSIS - Екатерина Александровна Киселева; Алишер Шавкатович Махмутходжаев; Галина Александровна Михеенко (The Publishing House Medicine and Enlightenment, 2022)
The aim of the research - research was to study the dynamics of some oxidative stress markers in patients with vulvar kraurosis receiving various treatment. Materials and methods. The women included to the study were divided into 3 groups. In the first group treatment consisted of photodynamic therapy and administration of Ethylmethylhydroxypyridine succinate for a month. In the second group the patients received photodynamic therapy only. In the third group the patients had a laser therapy of the perineal area. All the participants of the study were tested for malondialdehyde (MDA), 8-hydroxy-2-deoxyguanosine (8-OHdG), and superoxide desmutase (SOD) in blood serum before treatment, immediately after the therapy, and in a month after it. Results. It was found that women with vulvar kraurosis have high levels of MDA and 8-OHdG and low level of SOD in the blood serum. Concentration of these markers demonstrated the expected intensification of the cells oxidative damage immediately after the PDT using. The intensity of oxidative processes returned to the initial level in a month after PDT. In case of antioxidant therapy during a month after PDT, the levels of MDA and 8-OHdG were 2-4 times lower than the initial ones, the level of SOD increased and reached normal values. Immediately after laser therapy the levels of MDA and 8-OHdG decreased, the concentration of SOD increased. These parameters did not reach normal values and in a month were determined at their initial levels. Conclusion. The levels of MDA, 8-OHdG and SOD demonstrate the presence of oxidative stress in patients with vulvar kraurosis. At the same time, the method of kraurosis treatment is able to change a condition of the prooxidant and antioxidant systems in this category of patients.